Infertility due to low ovarian reserve - Treated by Matra basti-A case report - M U Arpitha; B M Bhavya; A G Athira (Wolters Kluwer Medknow Publications, 2023)
Reduction in quantity and quality of oocytes due to poor ovarian reserve is an important cause of infertility in many couples of reproductive age groups. Evaluating ovarian reserve and individualizing the therapeutic strategies are very important for optimizing the success rate. A 35-year-old female presented with difficulty in conception for 4 years. She was diagnosed with primary infertility due to a low anti-Mullerian hormone (AMH) level in a modern hospital. She was given assisted reproductive treatments at various hospitals and was not successful. Hence, the patient approached our outpatient department during the year 2021 for the management. A course of Matra basti (unctuous enema) was administered along with fertility awareness information without any oral medication. After the completion of treatment, the patient conceived naturally within the duration of 3 months. Low values of AMH are observed in low ovarian reserve causing infertility. Matra basti was found to be a beneficial procedure to treat infertility occurring due to low ovarian reserve in reproductive-aged women with no complications.